Insuficiência cardíaca em uma coorte de pacientes com síndrome coronariana aguda em um hospital de grande porte de Porto Alegre, RS - Silveira, Flávia Gama da (Universidade do Vale do Rio dos Sinos, 2011)
Currently, heart failure is a major public health problems in the world due to aging and changes in lifestyle of the population. Studies have shown that heart failure can be considered a common complication after AMI and thus far are modest studies that aim to prevent the development of heart failure in high-risk individuals compared to that aim new treatments for patients after the development of severe heart. Studies that aim at primary prevention of heart failure, with the identification of risk factors are of paramount importance, since it is a larger number of people and also contribute to the management of patients with overt cardiac failure. This study investigated the occurrence of heart failure (HF) and associated risk factors in a prospective cohort of patients with acute coronary syndrome, with 30 years or more, of both sexes admitted by the Institute of vascular medicine at the Hospital Mãe de Deus of Porto Alegre, RS. The sample size was given by the inflow of patients between May 2009 and July 2010. We determined the prevalence of previous HF; effect thirty days and six months after admission and prevalence in the period. The associations between risk factors and prevalence of IC in the period were analyzed using robust Poisson regression. Of the 125 patients enrolled, 62 (49.6%, 95% CI 40.8 to 58.4) had a previous diagnosis of HF. In thirty days we observed two new cases (0.02%, 95% CI 0.006 to 0.04) and in six months three new cases (0.02%, 95% CI 0.003 to 0.05). The prevalence of IC in the period was 53.6% (95% CI 44.8% to 62.3). In the adjusted analysis, remained associated with the outcome variables: low education (p = 0.01), previous AMI (p = 0.02) and angioplasty (p = 0.02).
Keywords: Síndrome coronariana agúda; Insuficiência cardíaca; Epidemiologia; Coorte; Acute coronary syndrome; Heart failure; Epidemiology; Cohort; ACCNPQ::Ciências da Saúde::Saúde Coletiva